The Influence Of Internal And External Factors In Measuring The Innovativeness Among Housing Developers In Peninsular Malaysia - Kamaruddeen, Ahmed Mohammed (2011)
The debate on the innovativeness status of the housing industry is ongoing and well documented in the literature. While some scholars opine that the housing industry is generally lagging behind other industries in terms of innovativeness, others contend that this claim does not reflect the actual condition of the industry which is innovative to a certain extent. Despite this, empirical studies in other industries have shown that certain firms’ internal and external factors do influence innovativeness of the firms. Coupled with the considerable attention on innovativeness in Malaysia in recent times, and the need for the Malaysian housing industry to be innovative in order to address the challenges it is facing, studies of innovativeness in the Malaysian housing industry are scarce.